Thousands of Famous People Are Closely Related to One Another - Karl Vachuska; Thomas J. Kelly (Genealogy, 2025)
Wealth and power have been recognized as being unequally concentrated within specific families. While research on social mobility has been limited to defined outcomes (e.g., occupation, income, and education) in specific contexts, the rise of big data has spurred broader network analysis. Using a comprehensive genealogical database of 30 million individuals in the Western Hemisphere, we analyzed how familial background, gender, and occupational domains influence the probability of individuals attaining “fame” in their lifetime. Individuals with famous parents are more likely to become famous themselves, especially males. Unexpectedly, we identified more than 10,000 famous individuals who are closely related, comprising 25.6% of all famous individuals in the entire dataset. While the underlying sample may have representativeness issues, the findings suggest that famous individuals are not isolated figures but often part of broader interconnected family networks.